PENGARUH KOMUNIKASI, BEBAN KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN - Nengah Sandi Pradnyana; Ni Made Ary Widyastini (Universitas Bina Taruna Gorontalo, 2023)
This study aims to examine and analyze the influence, namely: (1) communication, workload, and compensation on the performance of Crystal Kuta Hotel Bali employees; (2) communication on the performance of Crystal Kuta Hotel Bali employees; (3) workload on the performance of Crystal Kuta Hotel Bali employees; and (4) compensation for the performance of Crystal Kuta Hotel Bali employees. The population in this study were all employees of Crystal Kuta Hotel Bali, totaling 55 people. This research is included in the category of causal research using a quantitative approach. Data collection in this study was carried out by survey using a questionnaire. The data analysis method used is multiple linear regression analysis. The results of the study show that: (1) communication, workload, and compensation have a significant effect on the performance of Crystal Kuta Hotel Bali employees; (2) Communication has a positive and significant effect on the performance of Crystal Kuta Hotel Bali employees; (3) workload does not affect the performance of Crystal Kuta Hotel Bali employees; (4) Compensation has no effect on the performance of Crystal Kuta Hotel Bali employees. The research results are expected to be a consideration for hotel managers or company directors in determining employee communication, workload, and compensation so that employee performance increases and will affect guest satisfaction at the hotel.